(untitled) (Journal of Digital Business and Information Technology, 2024)
This research aims to investigate the effect of the duration of gadget use and the duration of study on logical abilities and its impact on the mathematics learning outcomes of students in the Informatics Engineering Study Program, STMIK Palangkaraya. The sample was taken using a purposive sampling technique, namely, 65 active students who had taken the Calculus 1 course. The data used were gadget usage duration data, study duration data, logical ability test results, and learning outcomes for the Calculus 1 course. Data was collected using observation techniques, questionnaires, tests, and documentation, and then path analysis was carried out to determine the direct and indirect influence of exogenous variables on endogenous variables with the help of Python. The results of the study indicate that logical ability has a positive but relatively weak influence on mathematics learning outcomes (path coefficient value: 0.1525), while the length of learning directly has a positive and fairly strong influence (1.1160). Learning results in mathematics and reasoning skills are not impacted by the amount of time spent using a device. The duration of gadget use has no effect on logical abilities or mathematical learning outcomes.